THE IMPACT OF THE FREQUENCY OF 7,12- DIMETHYLBENZ [Á] ANTHRACENE (DMBA) ADMINISTRATION ON THE FORMATION OF DYSPLASIA AND SQUAMOUS CELL CARCINOMA ON THE SKIN OF ALBINO MICE - Diana Muchsin; Khairuddin Djawad; Alwi A Mappiasse; Idham Jaya Ganda; Nasrum Massi; Gemini Alam (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACT Introduction: Dosage and frequency of 7,12-dimethylbenz[á] anthracene (DMBA) com- pound exposure suspected to affect the rapid growth of squamous cell carcinoma (SCC) in albino mice. Objective: find out the impact of DMBA exposure to dysplasia and SCC formation on albino mice. Methods: Twenty-five albino mice were divided into five groups, namely: Group 1 is the control (acetone), group 2 is 5 albino mice given four times DMBA100 µg exposure for eight weeks, group 3 is 5 albino mice were given eight times DMBA100 µg exposure for eight weeks, group 4 is 5 albino mice were given twelve times DMBA100 µg exposure for eight weeks, and group 5 is 5 albino mice were given sixteen times DMBA 100 µg exposure for eight weeks. Histopathological examination were conducted to assess histopathological feature including inflammation, dysplasia, and SCC. Results: There is a significant effect of the frequency of DMBA exposure to the clinical figure and against histopathological feature of the skin albino mice.Conclusions: Dosage and fre- quency of DMBA exposure affect the occurence of dysplasia and SCC, which are in- creasingly being DMBA exposure will accelerate the growth of SCC. The frequency of the most widely pose a SCC in DMBA 100 µg sixteen times exposure group, twice a week for eight weeks. Keywords: DMBA, dysplasia, squamous cell carcinoma